Long-term health effects of COVID-19 among patients in Croatian primary care settings - Popović, Branislava; Lesac Brizić, Ana; Ljubotina, Aleksandar; Zavidić, Tina; Tudor Špalj, Vedrana; Marković Štimac, Roberta; Fišić Jurković, Martina; Bašić Marković, Nina; Diminić Lisica, Ines; Vučak, Jasna; Radošević Quadranti, Nives (Frontiers in Medicine, 2026)
IntroductionThe COVID-19 pandemic has left lasting effects that extend beyond the acute phase of infection, with increasing evidence of long-term health consequences. This study aimed to assess the prevalence of post-COVID symptoms and conditions and to identify associated risk factors, including pre-existing chronic diseases, COVID-19 vaccination status, and severity of acute infection.MethodsThis retrospective cross-sectional study was conducted in 10 family medicine practices in Croatia. The data collected from medical records included demographics, COVID-19 vaccination status, SARS-CoV-2 infection history and severity, and documented health conditions before and after infection. Descriptive statistics were used to summarize the data. Group differences were analyzed using the independent samples t-test or χ2 test. Variables significant in univariate analyses (p < 0.05) were included into multivariate regression models. Multiple linear regression was used to identify predictors of COVID-19 severity, and binary logistic regression was applied to determine factors associated with post-COVID conditions. Results are presented as regression coefficients (β) or odds ratios (OR) with 95% confidence intervals (CI). A p-value < 0.05 was considered statistically significant.ResultsThe study included 1,423 participants (58.0% female; mean age 52.6 ± 17.2 years), of whom 82.4% had confirmed SARS-CoV-2 infection and 32.3% were unvaccinated. At least one chronic disease was present in 28.1% of participants. The most frequently reported post-COVID conditions were brain fog (4.9%), neurological disorders (4.7%), cardiovascular diseases (2.9%), shortness of breath (2.8%), obesity (2.7%) and mental health disorders (2.6%). Greater COVID-19 severity was independently associated with pulmonary disease (β = 0.22; p = 0.031) and older age, particularly 51–65 years (β = 0.31; p < 0.001) and ≥66 years (β = 0.50; p < 0.001). COVID-19 vaccination was associated with milder disease (β = −0.21; p < 0.001). Previous cardiovascular and musculoskeletal diseases significantly increased the risk of thromboembolism. Diabetes, obesity, and number of vaccine doses were predictors of brain fog, while neurological comorbidities predicted post-COVID mental health disorders.ConclusionPost-COVID symptoms and conditions represent an important long-term public health challenge. Family medicine physicians play a key role in early recognition, monitoring, and management of post-COVID sequelae, contributing to improved long-term patient outcomes.